2010
DOI: 10.1016/j.jinf.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous micafungin versus voriconazole for chronic pulmonary aspergillosis: A multicenter trial in Japan

Abstract: SUMMARYChronic pulmonary aspergillosis (CPA) is slowly progressive inflammatory pulmonary syndrome due to Aspergillus spp. The evidence regarding CPA treatment is limited. We conducted a randomized, multicenter, open-label trial comparing intravenous micafungin (MCFG) of 150-300 mg once daily with intravenous voriconazole (VRCZ) of 6 mg/kg twice on Day 1 followed by 4 mg/kg twice daily for the treatment of 107 inpatients with CPA to compare the efficacy and safety of both drugs as initial treatment in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 22 publications
6
136
1
8
Order By: Relevance
“…antifungal agents [14], the other oral azole therapy randomised against no antifungal therapy [83]. Most of the cohort studies do not clearly separate out the various subsets of CPA.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…antifungal agents [14], the other oral azole therapy randomised against no antifungal therapy [83]. Most of the cohort studies do not clearly separate out the various subsets of CPA.…”
Section: Treatment and Follow-upmentioning
confidence: 99%
“…micafungin in comparison with i.v. voriconazole in CPA patients [14]. Within the echinocandin class, a small double-blinded randomised controlled trial has shown caspofungin to be as effective as micafungin in improving health status in the CPA subset [97].…”
Section: Duration Of Antifungal Therapy For Cpamentioning
confidence: 99%
See 1 more Smart Citation
“…Antifungal therapy is very beneficial in CPA patients, as it reduces both morbidity and mortality. [6][7][8]30,[43][44][45][46] Little data exist on the development of CPA after PTB. Prospective clinical and epidemiological studies using the best diagnostic tools available are needed to ascertain its frequency in different places and among different ethnic groups.…”
Section: Future Directionsmentioning
confidence: 99%
“…Antifungal therapy is effective in ameliorating symptoms and reducing recurrence of haemoptysis in .60% of patients [4][5][6][7][8][9][10], and may reduce progressive lung fibrosis. Overall, treated CPA has a 20-33% short-term mortality and a 50% mortality over 5 yrs [6,11], but one small cohort showed that almost all patients with sarcoidosis and CPA had died within 2 yrs [12].…”
mentioning
confidence: 99%